Transformasi Supervisi Pendidikan di Era Digital: Tantangan dan Inovasi - Rahmah (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
The rapid development of digital technology has significantly transformed various aspects of education, including educational supervision practices. Supervision that was traditionally conducted through conventional methods is now required to adapt to digital dynamics to remain effective in improving learning quality. This article aims to examine the transformation of educational supervision in the digital era by analyzing the challenges encountered and the conceptual innovations that have emerged. This study employs a library research approach by reviewing academic sources such as books and national and international journal articles related to educational supervision and digital transformation. Data were analyzed using a descriptive-critical method to identify patterns of change, key challenges, and innovative supervisory practices. The findings reveal that educational supervision in the digital era faces challenges related to limited digital competence among supervisors, resistance within organizational culture, and shifts in supervisory communication patterns. Meanwhile, supervisory innovations have developed through the integration of digital technology, collaborative approaches, and reflective and performance-based supervision models. This study concludes that transforming educational supervision requires the integration of technological mastery, paradigm renewal, and strengthened professional competence to sustainably enhance learning quality.